Acceptance of Technology and e-Learning Among Undergraduate Business Students - Safaa A. M. Shaaban; Rehab G. Rabie (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Recently, e-Learning during the COVID-19 pandemic have affected all academic institutes all around the world. Academic institutes are facing challenges in keeping the education process in place. In order to keep the education system running at its capacity, academic institutions have had to quickly find solutions to adapt to the situation and overcome delays in many approaches and systems. The increased impact of the World Wide Web are leading to new and innovative ways of learning and education. educators and technology lead assumed that new e-learning system technologies and services enable activities that allow users to be active learners, actively participating in the on-line learning process. The objective of this paper is to examine the acceptance of e-education from the perspective of students and to raise their points of view. The methodology used is a self-reported survey and the PLA approach to confirm the findings. The main finding was that more training for teachers and students are essential to better implement technology in the education. Furthermore, the acceptance of e-Learning technology by students in higher education based on their training and orientations for the concept, while some students confirmed that their face-to-face education is more interaction.